Solar photocatalytic degradation of phenol using pyrolitic TiO2 films deposited inside a tubing - Rodríguez, Juan (2005)
Solar photocatalytic degradation of phenol was obtained using TiO2 films deposited inside glass tubing. TiO2 thin films inside tubing were obtained by spray-gel technique using a titanium isopropoxide solution conveniently diluted in ethanol. The gas carrier flux, air pressure and temperature were kept during deposition at 5 L/min, 200 kPa, and 200 °C, respectively. Experiments were performed using either the solar radiation or a 300 W lamp simulating the UVA solar radiation component. In order to concentrate the radiation a reflective surface was placed in the back part of the tube. The initial concentration of phenol solution was 20 ppm, and the phenol concentration during the experiment was followed using a standard colorimetric method when aminoantipirine reacts in the sample giving a colored complex. The volume of the phenol solution was limited with a solid aluminum rod placed axially to the glass tube. The obtained TiO2 films were amorphous, but after an annealing at 450 ºC for 1 h the films crystallize to anatase structure and present photocatalytic activity. The films morphology observed by scanning electron microscopy presented a uniform film and agglomerates of TiO2, the size of the agglomerates increases as Ti isopropoxide/ethanol molar ratio of the starting solution decreases. The precursor concentration solution and film thickness of TiO2 for phenol degradation was optimized.